Networks for Problem Solving at Schools: Participants’ Perception of Changes in their Professional Practice - Lapėnienė, Asta; Lukšytė, Dangira (Pedagogika, 2014)
The article focuses on teachers’ perception of changes resulting from their participation in school networks aimed at professional development of teaching professionals. Networks as an alternative form of professional development bring together the knowledge and skills of teachers across schools in order to promote shared learning through closer cooperation between schools. A total of 643 teachers from 119 Lithuanian schools of general education participating in the nationwide project “Networks of Learning Schools” responded to a qualitative online survey. For the purpose of the research presented in this article a secondary analysis was performed using self-collected datasets from the primary research. Three datasets of qualitative data were combined for the purposes of amplified analysis. The following conclusions can be drawn from the study. Teachers perceive their participation in professional networks as resulting in: 1) more active involvement in sharing professional knowledge both in networks inside the schools and in networks between the schools; 2) changes in learning culture, planning of teaching, achievement evaluation, collaboration between school community members, problem solving in school settings and educational research activities in school; 3) changes in student learning motivation and achievements, improved student skills in communication, problem solving, self-evaluation and learning to learn.